Identifikasi Senyawa Flavor Nonvolatil Pada Ikan Kembung Segar (Rastrelliger sp.) - Anisa Dwi Septhyani; Rusky Intan Pratama; Kiki Haetami; Evi Liviawaty (Jurnal Perikanan Unram, 2024)
Nonvolatile flavoring ingredients greatly affect food flavor and can affect food acceptability among consumers. The purpose of this study aimed to determine the mackerel's nonvolatile taste components. High Performance Liquid Chromatography (HPLC) was used to analyzed fish samples. 15 different kinds of amino acids were identified in the study: seven non-essential amino acids (glutamic acid, aspartic acid, arginine, alanine, glycine, serine, and tyrosine) and eight essential amino acids (lysine, leucine, valine, isoleucine, threonine, phenylalanine, methionine, and histidine). Glutamic acid (3.65%), aspartic acid (2.35%), lysine (2.37%), leucine (1.90%), arginine (1.46%), and alanine (1.41%) were discovered to be the main nonvolatile components in mackerel. Moreover, it was found that aspartic acid and glutamic acid provide the umami flavor, arginine, leucine, and lysine give the bitter taste, and alanine provides a sweet taste.